2022
DOI: 10.7759/cureus.28633
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Induced Seizures: A Meta-Analysis of Case Series and Retrospective Cohorts

Abstract: The adverse events and complications of coronavirus disease 2019 (COVID-19) continue to challenge the medical profession despite the worldwide vaccination against the severe acute respiratory coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19. Other than typical respiratory manifestations, COVID-19 also presents a wide range of neurological manifestations. This article underlines the pooled incidence of COVID-19-induced seizures in patients with epilepsy and without epilepsy. Following Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…52 According to a meta-analysis of case-series and retrospective cohorts among 71 PwE, 49 patients presented with seizures as an initial manifestation of COVID-19 infection with an incidence of 69% (54% −85%, p = 0.10, I 2 = 34%), which is much higher than the rate we reached in the present meta-analysis. 52 Also, the COVID-19 pandemic dramatically impacted the lives of PwE, partly due to reduced quality and accessibility of care for PwE, hence the increased seizure frequency. On the other hand, the social isolation might have made PwE more susceptible to more perceived anxiety and depression, potentially linked to the increased seizure frequency.…”
Section: Vaccination Benefits and Riskscontrasting
confidence: 61%
See 1 more Smart Citation
“…52 According to a meta-analysis of case-series and retrospective cohorts among 71 PwE, 49 patients presented with seizures as an initial manifestation of COVID-19 infection with an incidence of 69% (54% −85%, p = 0.10, I 2 = 34%), which is much higher than the rate we reached in the present meta-analysis. 52 Also, the COVID-19 pandemic dramatically impacted the lives of PwE, partly due to reduced quality and accessibility of care for PwE, hence the increased seizure frequency. On the other hand, the social isolation might have made PwE more susceptible to more perceived anxiety and depression, potentially linked to the increased seizure frequency.…”
Section: Vaccination Benefits and Riskscontrasting
confidence: 61%
“…Importantly, the chance of seizure activity‐related changes after COVID‐19 vaccines seems to be lower than COVID‐19 infection 52 . According to a meta‐analysis of case‐series and retrospective cohorts among 71 PwE, 49 patients presented with seizures as an initial manifestation of COVID‐19 infection with an incidence of 69% (54%−85%, p = 0.10, I 2 = 34%), which is much higher than the rate we reached in the present meta‐analysis 52 . Also, the COVID‐19 pandemic dramatically impacted the lives of PwE, partly due to reduced quality and accessibility of care for PwE, hence the increased seizure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of seizure occurrence after SARS-CoV-2 infection seems to be relatively high. 40 This jhas been observed for many other complications and other populations as well. For instance, in persons with epilepsy, the risk of increased seizure frequency after vaccinations seems to be less than that of SARS-CoV-2 infection.…”
Section: Sars-cov-2 Infection Vs Sars-cov-2 Vaccinesmentioning
confidence: 66%
“…The second study, 31 on the safety and efficacy of the Janssen vaccine, with a median follow-up of 121 days (range, 1-284 days), reported 9 new-onset seizures among 21 894 vaccine recipients (<0.1%) and 4 new-onset seizures among 21 882 placebo recipients (<0.1%). The last study, 34 on the safety and efficacy of the CoronaVac vaccine, with a median (IQR) follow-up of 43 days (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), reported 1 new-onset seizure among 6646 individuals (<0.1%) in the vaccine group and no events in the placebo group. After pooling the 3 studies, no statistical difference was identified between the vaccine and placebo groups (13/43 724 events [0.03%] in vaccine recipients and 5/40 612 events [0.012%] in placebo recipients; OR, 2.31; 95% CI, 0.86-6.23; P = .10, I 2 = 0%, τ2 = 0, Cochran Q P = .95) (Figure 3).…”
Section: Vaccine Vs Placebo Recipients In the Entire Blinded Phasementioning
confidence: 99%
See 1 more Smart Citation